A Comparative Study of Play Therapy and Child Friendly Constraint Induced Movement Therapy in Cerebral Palsy - Harini, K.; Raj, Gokila; Dhasaradharaman, Kannan (International journal of health sciences and research, 2022)
Background: Cerebral Palsy is a neuro developmental disorder caused by non progressive lesion in the developing brain. The aim of the study was to compare the effect of constraint induced movement therapy vs play therapy in cerebral palsy. Method: A sample of 20 patients within the age group of 4-8 years with cerebral palsy were randomly divided into two groups, Group A (n= 10) and group B (n= 10). The subjects in group A was treated with CIMT [Constraint induced movement therapy] and the subjects in group B was treated with Play therapy. The subject’s improvement on hand functions was assessed by Box and Block test (BBT) and Motor Activity Log Scale (MAL) and pre and Post test results were analysed. Result: The study concludes that there was statistically significant improvement of hand function in group A compared to group B in response to treatment Conclusion: Based on the result, this study concluded that child friendly constraint induced movement therapy is effective in spastic hemiplegic cerebral palsy than play therapy in cerebral palsy. Key words: CIMT, PLAY THERAPY, BBT, MAL .